Gabapentin inhibits the analgesic effects and nerve regeneration process induced by hepatocyte growth factor (HGF) in a peripheral nerve injury model: Implication for the use of VM202 and gabapentinoids for peripheral neuropathy - Lee, Nayeon; Nho, Boram; Ko, Kyeong Ryang; Kim, Sunyoung; Lee, Junghun (Molecular and cellular neuroscience, 2022)
Hepatocyte growth factor (HGF) is a multifunctional protein that plays a critical role in the angiogenic, neurotrophic, antifibrotic, and antiapoptotic activities of various cell types. It has been previously reported that intramuscular injection of pCK-HGF-X7 (or VM202), a plasmid DNA designed to express both native isoforms of human HGF (Pyun et al., 2010), significantly reduced the level of neuropathic pain in clinical studies as well as in a variety of animal models. In clinical studies, it has been observed that pCK-HGF-X7 appeared to give much higher pain-relieving effects in subjects not taking pregabalin or gabapentin, α2δ1 calcium channel blockers frequently prescribed for reducing pain in patients with diabetic peripheral neuropathy. In this study, we tested the effects of gabapentin on HGF-mediated pain reduction and nerve regeneration in vivo. Consistent with the data from clinical studies, gabapentin administration inhibited the pain reduction and axon regeneration effects mediated by HGF expression from pCK-HGF-X7. In the context of nerve regenerative effects, treatment with gabapentin or EGTA, a Ca2+ chelator, inhibited HGF-mediated axon outgrowth of injured sciatic nerves in vivo. Taken together, i.m. injection of HGF-encoding plasmid DNA ameliorated pain symptoms and enhanced the regeneration of injured nerves, and these therapeutic effects of HGF were significantly hindered by gabapentin treatment, suggesting the possible involvement of Ca2+ in the pro-regenerative activities of native HGF derived from treatment with pCK-HGF-X7. •In a CCI model, gabapentin administration significantly suppressed the HGF-mediated pain reduction.•In a nerve crush model, blockade of Ca2+ inhibited the HGF-induced regeneration of peripheral axons.•Gabapentin suppressed the protein level of c-Jun, and that of phosphorylated CREB in the DRG.•Gabapentin significantly inhibited the activation of the c-Met receptor in the injured sciatic nerve.